Identifying Implementation Science Characteristics for a Prenatal Oral Health eHealth Application. Issue 2 (March 2020) - Vamos, Cheryl A.; Green, Shana M.; Griner, Stacey; Daley, Ellen; DeBate, Rita; Jacobs, Tom; Christiansen, Steve
Background . Oral health is a significant public health issue; yet barriers to implementing the prenatal oral health guidelines into practice remain. This formative research aimed to identify key implementation science characteristics to inform the development of an eHealth application (app) to assist providers in implementing the prenatal oral health guidelines during prenatal visits. Method . Guided by the Consolidated Framework for Implementation Research, the clinic's infrastructure, workflow, and contextual factors were assessed via clinic observation, technology assessment, prenatal provider interviews ( n = 4), clinic staff interviews ( n = 8), and two focus groups with oral health providers ( n = 16). Results . System-level factors influencing future implementation were identified regarding structural characteristic, networks/communication, culture, external policy/incentives, relative advantage, complexity, design quality/packaging, knowledge/beliefs, and personal attributes. Discussion . Findings provided vital information and will directly inform the design and implementation of an eHealth app that aims to facilitate the translation of the interprofessional prenatal oral health guidelines into clinical prenatal oral health practices.